Acoustical studies of the solvation of ZnCl2 in methanol solutions - BOCH, Włodzimierz (Archives of Acoustics, 1977)
Measurements of the ultrasonic velocity at 15 MHz and the density of ZnCl2 solutions in methanol permitted determination of the dependence of the adiabatic compressibility of the solutions on temperature and concentration. The independence of the evaluated solvation numbers from the temperature and the insignificant decrease of their values with increasing solution concentration give evidence of the establishment in the solution of stable solvation complexes bound with complex ions ZnCl^(2–)_4.